Bacillus amyloliquefaciens CU33 Fermented Feather–Soybean Meal Product Improves the Crude Protein Digestibility, Diarrhea Status, and Growth Performance of Goat Kids - Tsung-Yu Lee; Yueh-Sheng Lee; Chean-Ping Wu; Kun-Wei Chan; Kuo-Lung Chen (Animals)
This study investigates the effects of replacing fish meal with fermented feather meal–soybean meal product (FFSMP) from Bacillus amyloliquefaciens CU33 in the starter on growth performance, relative health performance, and digestibility of Alpine goat kids. In trial 1, thirty-two Alpine goat kids (male) were randomly assigned to dietary supplementation of 2% feather meal–soybean meal mix (FSM), 2% fish meal, or replacing fish meal with 50% or 100% FFSMP (FFSMP-50 or FFSMP-100) in starter (n = 8). In trial 2, sixteen goat kids were selected after trial 1 and used in this digestion trial which began from 12 weeks old. The treatments were the same as in trial 1 (n = 4). In trial 1, the growth performance of the FFSMP groups was better than the FSM group at 0 to 10 weeks (p < 0.05). The fecal consistency index of the FFSMP-100 group was better than the FSM group at 0 to 5 weeks and 5 to 10 weeks. In trial 2, the crude protein (CP) digestibility of the FSM group decreased (p < 0.05). In conclusion, dietary supplementation with 2% FFSMP in goat kids’ diets can improve the growth performance, the CP digestibility, and diarrhea status, and it can completely replace the fish meal in starter diets.